APLIKASI ANALISIS DISKRIMINAN DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PRODUK McCafe (Studi Kasus: McDonald’s Jimbaran Bali) - RAMADHAN, TRISNA; SUMARJAYA, I WAYAN; ASIH, NI MADE; KENCANA, I PUTU EKA N. (E-Jurnal Matematika, 2018)
McDonald’s is one of fast food company that is growing rapidly. McDonald’s continues to innovate to satisfy customers. It introduced the concept of a cafe with the name McCafe. Because of the competition with other fast food restaurants, McDonald’s needs to improve the quality of McCafe favored by customers. Thus, this research was conducted to aim at getting the indicators that are best describing customers characteristic. This research use d discriminant analysis methods. Discriminant analysis was used to classify customers into groups of loyal customers or non loyal customers.. The indicator s that distinguishe d the decision of the customer to buy Mc Cafe Jimbaran product were affordable prices and locations that are easily accessible to customers. The formed discriminant function ha d an accuracy of 91,67 percent in classifying the customers.